Microsoft Unified XDR and SIEM solution handbook modernize and build a unified SOC platform for future-proof security - Boddu, Raghu; Lamppu, Sami (Packt Publishing Ltd., 2024)
Tired of dealing with fragmented security tools and navigating endless threat escalations? Take charge of your cyber defenses with the power of Microsoft's unified XDR and SIEM solution. This comprehensive guide offers an actionable roadmap to implementing, managing, and leveraging the full potential of the powerful unified XDR + SIEM solution, starting with an overview of Zero Trust principles and the necessity of XDR + SIEM solutions in modern cybersecurity. From understanding concepts like EDR, MDR, and NDR and the benefits of the unified XDR + SIEM solution for SOC modernization to threat scenarios and response, you'll gain real-world insights and strategies for addressing security vulnerabilities. Additionally, the book will show you how to enhance Secure Score, outline implementation strategies and best practices, and emphasize the value of managed XDR and SIEM solutions. That's not all; you'll also find resources for staying updated in the dynamic cybersecurity landscape. By the end of this insightful guide, you'll have a comprehensive understanding of XDR, SIEM, and Microsoft's unified solution to elevate your overall security posture and protect your organization more effectively.
Includes bibliographical references and index
Keywords: Computer security; Computer networks -- Security measures; Microsoft software; Sécurité informatique; Réseaux d'ordinateurs; Sécurité; Mesures; Logiciels Microsoft